2008
DOI: 10.1007/s10620-008-0540-3
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical and Histomorphometric Colon Remodelling in STZ-Induced Diabetic Rats

Abstract: The histomorphologic and passive biomechanical properties were studied in the mid-colon of 16 non-diabetic and 20 streptozotocin (STZ)-induced diabetic rats (50 mg/kg STZ, ip). The diabetic rats were divided into groups living 4 and 8 weeks after the induction of diabetes (n = 10 for each group). The mechanical test was a ramp distension of fluid into the colon in vitro. The colon diameter and length were obtained from digitized images of the segments at pre-selected pressures and at the no-load and zero-stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 36 publications
3
28
1
Order By: Relevance
“…The pathogenesis of such symptoms in diabetes mellitus is complex, multi-factorial with motor dysfunction, glycemic control, autonomic neuropathy, and psychological factors, and is not well understood [4] . Previous studies demonstrated changes in the morphological and biomechanical properties of the GI tract during diabetes, e.g., the wall thickness and stiffness of GI tract increased [5][6][7] . The structure or deformation changes may alter the relative positions of the mechanosensitive afferents (zero setting of the mechanosensitive afferents).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The pathogenesis of such symptoms in diabetes mellitus is complex, multi-factorial with motor dysfunction, glycemic control, autonomic neuropathy, and psychological factors, and is not well understood [4] . Previous studies demonstrated changes in the morphological and biomechanical properties of the GI tract during diabetes, e.g., the wall thickness and stiffness of GI tract increased [5][6][7] . The structure or deformation changes may alter the relative positions of the mechanosensitive afferents (zero setting of the mechanosensitive afferents).…”
Section: Introductionmentioning
confidence: 91%
“…For example the esophagus and colon were morphologically and biomechanically remodeled during the development of diabetes [6,7] . Abnormal levels of AGE and RAGE found in the present study may be associated with the GI remodeling in the GK diabetic rats.…”
Section: Age and Rage Changes In Gi Tract Of Gk Diabetic Ratsmentioning
confidence: 99%
“…Many animal and human studies have demonstrated that DM generally induces changes in the proliferation of different layers[5,8,10,41-51]. Increased expression of advanced glycation end of product (AGE) and AGE receptor (RAGE) has been demonstrated in the DM intestinal and colonic wall[49,51,52].…”
Section: Diabetes-induced Histomorphological and Biomechanical Changementioning
confidence: 99%
“…However, data on biomechanical changes in the diabetic colon is sparse. We have also investigated DM-induced biomechanical and morphometric remodeling in rat colon[10]. It was found in diabetic colon that the opening angle and residual strain became bigger and the stiffness of the colon wall increased with the duration of DM both in the circumferential and longitudinal directions (Figure 2).…”
Section: Diabetes-induced Histomorphological and Biomechanical Changementioning
confidence: 99%
See 1 more Smart Citation